Internalisasinilai Pendidikan Perdamaian Melalui Pemahaman Perbedaan Peran Gender dalam Pertunjukan Kesenian Reog Ponorogo - Nurwendah, Yusti Dwi; Nugrawiyati, Jepri (UIN Sunan Kudus, 2021)
Culture is the result of the construction of society through ideas and norms, which are reciprocal with public social life. Plural community life certainly creates its own challenges because it is vulnerable to conflict. This paper’s aim is to determine the differences in gender roles in Reog art and the valuescontained in. Gender differences in their identities and roles both naturally and as result of social construction often arise conflicts within them. One feels as a passive and subordinating, while other as an active and dominating. This dichotomy of roles, traits, and positions between men and women born by the concept of gender causes its own stereotypes, so that misunderstandings and conflicts arise between one and another. The art of Reog Ponorogo essentially internalizes the values of peace as an effort to cultivate spirit of peace and mutual tolerance. The value of peace education is displayed through understanding diversity of men and womens’ identities and roles.